2018
DOI: 10.1590/1413-70542018421002117
|View full text |Cite
|
Sign up to set email alerts
|

Substrates and irrigation levels for growing desert rose in pots

Abstract: In the past decades, desert rose has become a very popular ornamental plant, especially among collectors, due to its exotic and sculptural forms. However, it has been grown on a commercial scale only recently, and little is known about how to best manage it as a container-grown plant, or even which potting medium (substrate) to recommend. Therefore, the aim of this study was to investigate the interactions between potting media and irrigation levels for growing desert rose as a potted ornamental plant. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…On the other hand, the coconut fiber substrate mixed with sand (1:1, v/v) or vermiculite (1:1, v/v), showed satisfactory initial growth in Adenium at 45 days after the seedlings transplanting and the absence of additional fertilization (COLOMBO et al, 2018). In the same study, it was verified that the effect of the mentioned substrates persisted during a period of seven months, similar to the substrate recommendation for Adenium commercial cultivation.…”
Section: Adenium Growth Management Potting Media and Irrigationsupporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, the coconut fiber substrate mixed with sand (1:1, v/v) or vermiculite (1:1, v/v), showed satisfactory initial growth in Adenium at 45 days after the seedlings transplanting and the absence of additional fertilization (COLOMBO et al, 2018). In the same study, it was verified that the effect of the mentioned substrates persisted during a period of seven months, similar to the substrate recommendation for Adenium commercial cultivation.…”
Section: Adenium Growth Management Potting Media and Irrigationsupporting
confidence: 69%
“…To produce potted ornamentals plants, it is available different types of potting media that can be used alone or mixed (GRUDA, 2012). However, to Adenium commercial production as potted plant, just a few studies are found regarding potting media and irrigation management (COLOMBO et al, 2018).…”
Section: Adenium Growth Management Potting Media and Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…These affirmations are verified by Colombo et al (2018b) who concluded that desert rose seedlings must be kept in substrates with capacity of water retention superior to 60% of irrigation for their growth not to be compromised. These conditions, in fact, were not provided to the plants dues to the watering shifts adopted, suggesting that the use of hydrogel in different doses was not sufficient to keep the minimum required moisture for the seedlings growth.…”
Section: Use Of Hydrogel In Different Substrates For Production Of Dementioning
confidence: 78%
“…It is worth mentioning that, in addition to the premises required for a good substrate, substrates should be made with materials locally available or near the production location, since they may represent significant increase in production costs, particularly when commercially used or acquired (Monteiro Neto et al, 2016). The desert rose, for being included in the group of species economically profitable only during the last decade, still counts on incipient information on the production system, and on recommendation of substrates for production of seedlings (Colombo et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%